THE ANALYSIS OF POLITENESS STRATEGIES IN DIRECTIVE UTTERANCES IN THE MOVIE MISSION: IMPOSSIBLE – FALLOUT - Eko Setyawan; Christina Maya Iriana Sari (Humaniora Scientia, 2021)
This research is entitled "Analysis of Politeness Strategies in Directive Speech in Mission:Impossible - Fallout". The purpose of this research is to find out the utterance that tellssomeone and contains elements of politeness strategies. The object of this research isMission: Impossible – Fallout. It is a 2018 American spy film directed by ChristopherMcQuarrie. In this study, the method used is descriptive qualitative because the researcherwill examine and interpret the data. The data found is in the form of a dialog. The step to getdata is to collect data sources from subtitles. After that, the researcher reads, selects, andanalyzes dialogues containing politeness strategies in directive speech. The results of thisstudy, researchers found 70 data. Then, from 70 data, there are 2 types of politenessstrategies, namely positive politeness, and negative politeness. Positive politeness is found in8 data, negative politeness is found in 62 data. In analyzing the manner of politenessstrategies in directive speech, the researcher uses the social dimension, therefore it is relatedto the solidarity social distance scale, status scale, and formality scale, and two functional.Keywords: Directive Utterances, Politeness Strategy, Positive Politeness, NegativePoliteness, Social Dimensions, Pragmatic, Sociopragmatic, Speech Acts, Mission:Impossible - Fallout